(3Yjhf GdCfHGA aj WHbGJ GdCWHGAs - (3GHf CHj GUjHYI , ehab GdOjf CHh GdYHGS CMeO Hf GdbGSe Hf NdjaI Hf jhfS GdSYOj GdNRQLj,J (B668 (3g` s
(3ChdgG (B:s
(3hHYO, aEfg deG cGfJ UfGYI GdWH ef CaVd GdUfGYGJ QCjJ Cf CPcQ ai gPG GdcJGH fcJG hYjhfG ai eQGJH GdeJejRjf ef GdCWHGA s
(3BNQgG (B:s
(3Je GdHGH GdYGTQ ef cJGH Yjhf GdCfHGA s
(3GfXQ CjkVG Qbe (B346s
(3Qbe (B1144 (3JGQjNs
(3ChQGb ef GdLRA GdChds
(3YdjgG hbajI SfI (B1067(3g`s
(3hbO UhQJ ef Chd GdcJGH hHVY ef BNQg s
(3fSNI QGHYI s
Keywords: (3GdJGQjNs